Impact of light–matter coupling strength on the efficiency of microcavity OLEDs: a unified quantum master equation approach - Siltanen, Olli; Luoma, Kimmo; Daskalakis, Konstantinos S. (Royal Society of Chemistry (RSC), 2026)
Controlling light-matter interactions is emerging as a powerful strategy to enhance the performance of organic light-emitting diodes (OLEDs). By embedding the emissive layer in planar microcavities or other modified optical environments, excitons can couple to photonic modes, enabling new regimes of device operation. In the weak-coupling regime, the Purcell effect can accelerate radiative decay, while in the strong-coupling regime, excitons and photons hybridize to form entirely new energy eigenstates with altered dynamics. These effects offer potential solutions to key challenges in OLEDs, such as triplet accumulation and efficiency roll-off, yet demonstrations in the strong-coupling case remain sparse and modest. To systematically understand and optimize photodynamics across the different coupling regimes, we develop a unified quantum master equation model for microcavity OLEDs. Applying the model, we identify the conditions under which each coupling regime performs optimally. Strikingly, we find that maximizing the coupling strength does not necessarily maximize internal quantum efficiency. Instead, the efficiency depends on a delicate balance between material and cavity parameters.